2010
DOI: 10.1590/s0102-695x2010000400002
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase and butyrylcholinesterase inhibitory activity of some selected Nigerian medicinal plants

Abstract: RESUMO: "Atividade inibitória da acetilcolinesterase e butirilcolinesterase de algumas plantas medicinais da Nigéria". As plantas podem ser úteis para estimular a memória, bem como serem usadas para combater o envelhecimento. Vinte e duas plantas, de dezesseis famílias, foram investigadas in vitro oara verificar sua atividade inibidora das enzimas acetilcolinesterase (AChE) e butirilcolinesterase (BuChE) pelo método espectrofotométrico de Ellman in situ e métodos de bioautografia utilizando fisostigmina como p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 16 publications
2
22
0
1
Order By: Relevance
“…The extracts showed dose-dependent cognitive enhancing activity with Peltophorum pterocarpum having shorter escape latency time of 14.60 + 1.55 at 8 mg/kg and thus appears to have better cognitive enhancing ability when compared with Morinda lucida with escape latency of 23.33 + 4.33 at the same dose. The cognitive enhancing activity observed in this study can be due to previously reported cholinesterase inhibitory property of these plants (Elufioye et al, 2010) since acetyl cholinesterase inhibitors are known to counteract scopolamine induced amnesia (Lee et al, 2009). This is probably because the effects of scopolamine in learning and memory are also mediated by cholinergic neurons in the ventral forebrain, particularly in those arising from the medial septal nuclei or the diagonal band of Broca and projecting to the hippocampus (Bejar et al, 1999).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The extracts showed dose-dependent cognitive enhancing activity with Peltophorum pterocarpum having shorter escape latency time of 14.60 + 1.55 at 8 mg/kg and thus appears to have better cognitive enhancing ability when compared with Morinda lucida with escape latency of 23.33 + 4.33 at the same dose. The cognitive enhancing activity observed in this study can be due to previously reported cholinesterase inhibitory property of these plants (Elufioye et al, 2010) since acetyl cholinesterase inhibitors are known to counteract scopolamine induced amnesia (Lee et al, 2009). This is probably because the effects of scopolamine in learning and memory are also mediated by cholinergic neurons in the ventral forebrain, particularly in those arising from the medial septal nuclei or the diagonal band of Broca and projecting to the hippocampus (Bejar et al, 1999).…”
Section: Resultssupporting
confidence: 66%
“…K Heyne and Morinda lucida (L) Rubiaceae are commonly found in recipes used as memory enhancer or anti-aging in Nigeria ethno-medicine. The leaves of these plants have been previously reported to inhibit cholinesterase (Elufioye et al, 2010., Sridharamurthy et al, 2012) an enzyme that causes a decline of ACh in the brain by breaking it down. Acetylcholine is critical for an adequately functioning memory and it is the subject of the major researches for treatment of memory defects like those found in Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancement of AchE activity causes more acetylcholine degradation and consequent reduction in acetylcholine receptor stimulation which leads to a decrease in cholinergic neurotransmission and related functions such as cell proliferation and enhanced apoptosis [43][44][45]. Deficiency in acetylcholine and consequent cholinergic neurotransmissions is one of the cognitive symptoms of Alzheimer's disease (AD) [46]. It has been also shown that, acetylcholine is involved in reduction of LPO by scavenging superoxide anions [47].…”
Section: Discussionmentioning
confidence: 99%
“…The hydrolytic enzyme, cholinesterase, regulates ACh levels by breaking down this neurotransmitter in many tissues. AChE activity is altered in response to redox imbalance and affected by various degree of injury to the organism which can stimulate rapid ACh degradation and consequently, decreased stimulation of ACh receptors leading to negative effects on cholinergic neurotransmission as well promotion of cognitive impairment (Elufioye et al, 2010;Abdalla et al, 2013 The neurotransmitter, dopamine, is produced from the amino acid, tyrosine, through the catalytic action of tyrosine hydroxlase (TH) which is the rate-limiting enzyme in the pathway. (Daubner and Wang, 2011).…”
Section: Discussionmentioning
confidence: 99%